2019
DOI: 10.3390/nu11102416
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Approaches in the Studies Assessing Associations between Human Milk Immune Composition and Allergic Diseases: A Scoping Review

Abstract: A growing number of studies are focusing on the associations between human milk (HM) immunological composition and allergic diseases. This scoping review aims to identify statistical methods applied in the field and highlight pitfalls and unmet needs. A comprehensive literature search in MEDLINE and Embase retrieved 13,607 unique records. Following title/abstract screening, 29 studies met the selection criteria and were included in this review. We found that definitions of colostrum and mature milk varied acro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
(158 reference statements)
0
3
0
Order By: Relevance
“…Heterogeneity, lack of standardisation of sample collection and processing within and between studies is a common challenge in breast milk research (64)(65)(66). The studies included in this review were no exception and, like others before us, we identified a need for greater standardisation and clearer reporting of sample collection and processing methods (64,66).…”
Section: Methodological Considerations Within Studiesmentioning
confidence: 75%
See 1 more Smart Citation
“…Heterogeneity, lack of standardisation of sample collection and processing within and between studies is a common challenge in breast milk research (64)(65)(66). The studies included in this review were no exception and, like others before us, we identified a need for greater standardisation and clearer reporting of sample collection and processing methods (64,66).…”
Section: Methodological Considerations Within Studiesmentioning
confidence: 75%
“…This is a common feature for young and fast-growing research fields as the coherence in methods and other study features are continually developing. Furthermore, heterogeneity, lack of standardisation of sample collection and processing within and between studies is a known challenge in breast milk research (64)(65)(66). The studies included in this review were no exception and, like others before us, we identified a need for greater standardisation and clearer reporting of sample collection and processing methods which we discuss below (64,66).…”
Section: Discussionmentioning
confidence: 83%
“…As interest in DHM use and human milk science increases,12 more research is undoubtedly warranted to unravel potentially underlying mechanisms, the complex characteristics of DHM and its potential health effects 13. While systematic reviews are used to discover and identify, analyse and synthesise already existing evidence relevant to a certain research topic and question,14 scoping reviews have become particularly useful when a topic is underinvestigated as a more prominent method of summarising research information 15.…”
Section: Introductionmentioning
confidence: 99%